Batman, the Dark Knight Unwrapped - Finch, David, 1972- (New York : DC Comics, 2015)
"A sketch edition of some of comics superstar David Finch's greatest Batman stories from Batman: The Dark Knight, DC Comics: The New 52 and more! This fantastic unwrapped collection features tales of the Dark Knight written and pencilled by David Finch. Encompassing David's work from Batman: The Dark Knight to the re-launch in the New 52, this volume features the stunning artwork and compelling stories about the supernatural and the esoteric areas of Gotham City. Collects Batman: The Dark Knight #1-3, Batman: The Return #1 and Batman: The Dark Knight (Vol 2) #1-7 and 9 in black and white format"--
Keywords: COMICS & GRAPHIC NOVELS / Superheroes